At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure, let's solve the equation step by step:
Given equation:
[tex]\[ 12i = 34 - 2(8i + 3) \][/tex]
### Step 1: Distribute the -2 on the right side
First, distribute the -2 to both terms inside the parentheses:
[tex]\[ 2(8i + 3) = 2 \cdot 8i + 2 \cdot 3 = 16i + 6 \][/tex]
Substitute this back into the equation:
[tex]\[ 12i = 34 - (16i + 6) \][/tex]
### Step 2: Simplify the equation
Next, simplify the right side by subtracting [tex]\(16i + 6\)[/tex] from 34:
[tex]\[ 12i = 34 - 16i - 6 \][/tex]
Combine the constants on the right side:
[tex]\[ 12i = 28 - 16i \][/tex]
### Step 3: Move all terms involving [tex]\(i\)[/tex] to one side
Move the term involving [tex]\(i\)[/tex] on the right side to the left side by adding [tex]\(16i\)[/tex] to both sides:
[tex]\[ 12i + 16i = 28 \][/tex]
### Step 4: Combine like terms
Add the coefficients of [tex]\(i\)[/tex] together:
[tex]\[ 28i = 28 \][/tex]
### Step 5: Solve for [tex]\(i\)[/tex]
Finally, divide both sides by 28 to isolate [tex]\(i\)[/tex]:
[tex]\[ i = \frac{28}{28} = 1 \][/tex]
### Conclusion
Thus, the solution to the equation [tex]\(12i = 34 - 2(8i + 3)\)[/tex] is:
[tex]\[ i = 1 \][/tex]
Given equation:
[tex]\[ 12i = 34 - 2(8i + 3) \][/tex]
### Step 1: Distribute the -2 on the right side
First, distribute the -2 to both terms inside the parentheses:
[tex]\[ 2(8i + 3) = 2 \cdot 8i + 2 \cdot 3 = 16i + 6 \][/tex]
Substitute this back into the equation:
[tex]\[ 12i = 34 - (16i + 6) \][/tex]
### Step 2: Simplify the equation
Next, simplify the right side by subtracting [tex]\(16i + 6\)[/tex] from 34:
[tex]\[ 12i = 34 - 16i - 6 \][/tex]
Combine the constants on the right side:
[tex]\[ 12i = 28 - 16i \][/tex]
### Step 3: Move all terms involving [tex]\(i\)[/tex] to one side
Move the term involving [tex]\(i\)[/tex] on the right side to the left side by adding [tex]\(16i\)[/tex] to both sides:
[tex]\[ 12i + 16i = 28 \][/tex]
### Step 4: Combine like terms
Add the coefficients of [tex]\(i\)[/tex] together:
[tex]\[ 28i = 28 \][/tex]
### Step 5: Solve for [tex]\(i\)[/tex]
Finally, divide both sides by 28 to isolate [tex]\(i\)[/tex]:
[tex]\[ i = \frac{28}{28} = 1 \][/tex]
### Conclusion
Thus, the solution to the equation [tex]\(12i = 34 - 2(8i + 3)\)[/tex] is:
[tex]\[ i = 1 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.